PENGARUH KINERJA PEGAWAI SEBAGAI STRATEGI BAURAN PEMASARAN JASA PENDIDIKAN DI SD NEGERI 5 DAMAR - Anastasya (Program Studi Manajemen Pendidikan Islam, 2022)
Employee performance is the work ability of an employee. School employee performance is a work achievement that must be achieved by an employee in an educational institution. Employee performance is part of the marketing mix of educational services, namely HR (human resources). This study aims to analyze the effect of employee performance as a marketing mix strategy for education services at SD Negeri 5 Damar. The research method used is a qualitative approach with descriptive analysis. This research was conducted by means of observation through data collection using questionnaires. The research respondents were 11 people consisting of 1 principal, 8 teachers, and 2 administrators. This study also uses a literature review of several research results, e-books, articles, and case studies that occur in the field. The results of this study are the problem of employee performance, employee impact as a marketing mix strategy at SD Negeri 5 Damar, and problem solving efforts